Fifteen minute consultation: headache in children under 5 years of age. Issue 5 (13th July 2013) - McCrea, Nadine; Howells, Rachel
Abstract : Headache occurring in children under the age of 5 years may cause a high level of anxiety in both parents and medical professionals. Crucial to a consultation about this problem will be to actively seek out clues to sinister pathologies, and investigate or reassure as appropriate. Making a positive diagnosis of a primary headache disorder where one exists is also important; however, in young children, headache does not always conform to well-established diagnostic criteria. This short guide provides a practical overview using the scenario of a new referral to the outpatient clinic.